RANCANG BANGUN MESIN PRES BAGLOG 4 LUBANG UNTUK MENINGKATKAN PRODUKTIVITAS PEMBUATAN BAGLOG JAMUR TIRAM - Abdul Salam; Abram Tangkemanda; Nurul Aulia (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Oyster mushroom cultivation partners located in Simbang District, Maros Regency said that the demand for mushrooms for the South Sulawesi region is very high, especially in the city of Makassar per day can reach 500 kg. Making baglogs whose pressing is still done manually is less efficient because can be made one baglog in 2 minutes or 30 baglogs / hour, so this is less effective and efficient because baglog production is very low. The design of the 4-hole baglog press machine has the main components: frame, 6.5 HP gasoline engine, gearbox, transmission system, pressing rod, adjust post, and baglog direction funnel. The working principle press machine is to convert rotational motion into translational compressive force. If the engine is turned on, the engine rotation is distributed through the v-belt then the output of the gearbox will drive the main shaft through the chain transmission which passes the force to the baglog pressing shaft rotating disc to form a baglog. Based on the results of the design of the baglog press machine, it can be increase the baglog production capacity by about 120 baglogs/hour with a uniform porosity, which is 0.725 grams/cm2.